Characteristic Polynomial and Eigenvalues of Anti-adjacency Matrix for Graph K_m ⨀ K_1 and H_m ⨀ K_1 - Putra, Ganesha Lapenangga (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2024)
Let G=(V,E) be a simple and connected graph. The adjacency matrix G is a representation of a graph in the form of a square matrix, with the size of the matrix determined by the order G. By defining a graph into a matrix, lots of research related to a spectrum has been done by researchers. Later, they defined the anti-adjacency matrix as a matrix obtained by subtracting a matrix with all entries equal to one and the adjacency matrix G. In this paper, we determine the characteristic polynomial of matrix anti-adjacency for corona product between complete graph K_m and K_1and hyper-octahedral graph H_m and K_1 with the eigenvalues.